Nursing, Caregiving and Psychological support in Chronic Disorders of Consciousness: a scoping review.: Nursing and Caregiving in DoC - Raciti, Loredana; Corallo, Francesco; Manuli, Alfredo; Calabrò, Rocco Salvatore (Acta Biomedica Atenei Parmensis, 2021)
Background and aims: The major disorders of consciousness include Coma, Vegetative State, and Minimally Conscious State. The care and the management of patients with Disorders of Consciousness (DOC) have raised several important ethical, social and medical issues. Aim of this review is to evaluate the role of nursing and psychological support in DOC management, in order to improve the quality of life of both patients and their caregivers.Methods: Studies dealing with DOC, nursing and caregiving pubblished in the last 20 years (from January 2000 to June 2020) were identified by searching on PubMed, Web of Science and Cochrane databases.Results: This review highlights the important role of DOC carevigers in the complex management of these frail patients, as well as the need for a specific support and counselling of caregivers. This psychological support may be given by nurses, as they are the healthcare professionals more involved in DOC care and cure.Discussion: Over the last years, specific recommendations for the assessment and rehabilitation of patients with DOC have been promulgated by neurorehabilitation organizations to provide some guidelines for the care and cure of such frail patients. Indeed, DOC patients need a multidisciplinary approach in which both caregivers and nurses have a pivotal role.Conclusions: As the family is a critical and fundamental aspect in the management of DOC patients, it should be considered an integral part of care in the future guidelines.